The Effectiveness of the Implementation of the Mobile Session in the Case of Isbat Nikah (Case Study at Takengon Syar'iyah Court Class IB): Efektivitas Pelaksanaan Sidang Keliling Dalam Perkara Isbat Nikah (Studi Kasus Pada Mahkamah Syar’iyah Takengon Kelas IB) - Sarwani, Novita (El-Hadhanah : Indonesian Journal Of Family Law And Islamic Law, 2022)
Isbat marriage is the ratification of marriage for the Muslim community which is carried out by the Religious Court/Syar'iyah Court in accordance with applicable regulations and isbat marriage is also an effort by the government for people who do not have a marriage certificate, so that they can re-establish their marriage. One of the annual programs from the government in this matter is the implementation of the marriage isbat circuit court program carried out by the Syar'iyah Court of Takengon Class IB. Based on the data received from the Takengon Syar'iyah Court and the Office of Religious Affairs (KUA) of Linge District regarding the isbat of marriage, there are still people who do not have a Marriage Certificate. Therefore, the problem of this thesis is how to carry out a mobile trial in the Isbat Marriage case at the Syar'iyah Court of Takengon Class IB, how is the effectiveness of the implementation of the circuit court in the Isbat Marriage case at the Syar'iyah Court of Takengon Class IB. The methods used in this paper are field research, library research using data collection techniques such as observation, interviews, and documentation conducted at the Syar'iyah Court of Takengon Class IB. The results of this study are the process of carrying out the trial in the settlement of isbat marriage cases through a mobile court held by the Syar'iyah Court of Takengon Class IB in Linge District in Central Aceh in the trial process there is no difference with the trial process at the court office starting from the procedures, the execution is the same. It only differs in the place where the trial is held. The results showed that based on the explanation of the theory of legal effectiveness, there were several theories that had not been fulfilled, so that the implementation of the circuit court in the isbat marriage case had not been effective.